Evolution of Grain and Seed Cleaning Equipment in Russia - V. M. Drincha; Yu. S. Tsench (Сельскохозяйственные машины и технологии)
The authors determined that in the development of grain production technical support, the main role was played by such a system-forming factor as the transition of the country’s grain enterprises to private ownership. Over the past 30 years, private companies and individuals became grain owners (with the exception of a small share). The authors substantiated the necessity for the development of grain-seed cleaning equipment in Russia. They showed the relevance of developing a new scientific and technical policy in the field of machine development support for grain production and its optimal functioning.(Research purpose) To carry out an evolutionary analysis of grain and seed cleaning equipment development and functioning, to determine the main periods and system-forming factors of its development.(Materials and methods) The authors applied the historical-analytical method in addition to technical systems. As research objects, they studied the original works of domestic and foreign authors for more than 100 years: monographs, dissertations, reports of research institutions, machine testing stations protocols, scientific journals, conference materials, as well as descriptions for domestic and foreign patent documentation.(Results and discussion) They described the evolution of grain-seed cleaning equipment development over the past 150 years: from the simplest tools to complex machine systems of industrial flow technologies. The authors presented the main characteristics of grain-seed cleaning machines and indicators of grain mixtures separation by sieves processes at various stages.(Conclusions) The main system-forming factors influencing the technical support of grain production such as: socio-economic conditions; soil and climatic conditions; science and technology policy; organizational factors were revealed. They substantiated four stages of its development: the first (1870-1930) – the use of the simplest manual machines of foreign production; the second (1930-1950) – the birth of domestic production of grain-seed cleaning equipment; the third (1950-1991) – the transition from the use of separate machines to industrial flow technologies; the fourth (1991 – to the present) – the transition from traditional flow technology to a variety of technologies and machines.